Comparison, Outcome of Single Layer Interrupted Extramucosal Repair VS Double Layer Continuous Repair (Journal of Fatima Jinnah Medical University, 2018)
Objective: To conclude that Single layer interrupted extramucosal intestinal anastomosis is a safer technique with fewer complications than double layer continuous intestinal anastomosis. Study Design: Prospective Analytical Duration: Surgical Unit I, Sir Ganga Ram Hospital from March 2010 to March 2012. Setting & Methodology: Total of 75 cases were included for this study and were divided in two groups. Group A, 40 cases in which gut anastomosis was performed with single layer extramucosal interrupted fashion. Polyglactin (Vicryl TM), (2/0) material was chosen over round body needle. Group B, 35 cases underwent conventional double layer anastomosis with Polyglactin (Vicryl TM), (2/0). The outcome in terms of anastomotic leak was compared in the two groups. Results: The two groups were randomized and evenly matched by age, sex and diagnosis Postoperative complications were assessed.The main postoperative complications anastomotic leak was studied. In the total 75 patients studied anastomotic leak was seen in 6 patients. Two from group A and Four from group B. Conclusion: Single layer interrupted technique is a safe technique with fewer complication and marked advantages so can be should be used in preference to double layer technique for intestinal anastomosis.